Embolization with larger-caliber coils can increase packing density: Evidence from the pilot phase of a randomized trial. Issue 1 (February 2017) - Cloutier, Francis; Khoury, Naim; Ghostine, Jimmy; Farzin, Behzad; Kotowski, Marc; Weill, Alain; Roy, Daniel; Raymond, Jean
Background and purpose: Endovascular coil embolization of cerebral aneurysms is associated with suboptimal angiographic results in up to 20–30% of patients. Coil packing density has been used as an index of the success of the initial procedure. The trial sought to study the effects of using 15-caliber coils, as compared with 10-caliber coils, on packing density. Methods: Does Embolization with Larger coils lead to better Treatment of Aneurysms (DELTA) is an investigator-initiated multicenter prospective, randomized, controlled clinical trial. Patients are randomized 1:1 to embolization with either 10-caliber coils exclusively (control group) or the highest safely achievable proportion of 15-caliber coils and 10-caliber coils if necessary (intervention group) in 4–12-mm aneurysms. The endpoint of the pilot phase of the trial was the capacity to increase packing density of the initial procedure, calculated using a mathematical transformation of the dimensions entered into the case report forms. Secondary outcomes included the total number of coils used per aneurysm, total fluoroscopy time, initial angiographic outcomes and any adverse or undesirable event. Results: Seventy patients were recruited between June 2014 and November 2015. Compared with 10-caliber coils, the 15-caliber coil group had a higher median packing density (44% vs 24%, p  = 0.017). Results of other outcome measures were similar for the two groups. Conclusion: Coiling of small and medium aneurysms randomized to 15-caliber coils achieved higher packing densities compared with coiling using 10-caliber coils.